GERONTEKNOLOGI BERBASIS KECERDASAN BUDAYA DAN DESAIN BERPUSAT MANUSIA: MEWUJUDKAN KEHIDUPAN LANJUT USIA BERKUALITAS DAN BERMARTABAT - Dony Hermawan (Bajang Institute, 2026)
The global population aged 60 and over is projected to double to approximately 2.1 billion by 2050, posing unprecedented demographic, economic, and caregiving challenges. Current models focus too much on clinical decline and neglect psychological resilience and cultural belonging, perpetuating fragmented eldercare. This study reconceptualizes aging as a culturally bound human experience, mediated by technology but grounded in dignity. Using a human-centered design framework, Hofstede's dimensions, and Nussbaum's Capacity Approach, the study formulated a model of